2013
DOI: 10.1063/1.4829437
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotics for inhomogeneous Dirichlet initial-boundary value problem for the nonlinear Schrödinger equation

Abstract: We consider the inhomogeneous Dirichlet initial-boundary value problem for the nonlinear Schrödinger equation, formulated on a half-line. We study traditionally important problems of the theory of nonlinear partial differential equations, such as global in time existence of solutions to the initial-boundary value problem and the asymptotic behavior of solutions for large time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In these papers, the existence of modified scattering for the Dirichlet and Neumann problems for the Klein-Gordon equation with cubic nonlinearities on half-line were considered. We also mention the papers [27][28][29] for related problems in the case of the nonlinear Schrödinger equation and [45,46] for the case of the Thirring model.…”
Section: Setting Of the Problemmentioning
confidence: 99%
“…In these papers, the existence of modified scattering for the Dirichlet and Neumann problems for the Klein-Gordon equation with cubic nonlinearities on half-line were considered. We also mention the papers [27][28][29] for related problems in the case of the nonlinear Schrödinger equation and [45,46] for the case of the Thirring model.…”
Section: Setting Of the Problemmentioning
confidence: 99%
“…Although nonlinear Schrödinger equations with inhomogeneous boundary conditions have been studied to some extent, most of these papers were devoted to inhomogeneous Dirichlet boundary conditions; see [10], [4], [5], [8], [6], [26], [9], [14], [21], [16], [3], [22], [24]. There are relatively less results on inhomogeneous Neumann boundary conditions; see [5], [7], [15], [23], [24].…”
Section: Literature Overviewmentioning
confidence: 99%
“…Another method for analyzing one dimensional initial-boundary value problems, based on the Riemann-Hilbert approach, was introduced in [20]. By this method, in [21], it was shown that long range scattering occurs in CNLS equation. The advantage of Riemann-Hilbert approach is that it can be applied to non-integrable equations with general inhomogeneous boundary data, but some technical problems have to be overcame (see [22,[24][25][26]).…”
Section: Introductionmentioning
confidence: 99%